Estimate of trunk inclination during fast movements by inertial sensing - Bergamini, E.; Melis, M.; Lentola, A.; Camomilla, V. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
The purpose of this study was to identify a reliable algorithm to estimate the inclination of a trunk-mounted inertial measurement unit (IMU) during fast movements and to test its subject- and task-specificity. Ten amateur football players performed three times the approach phase of the drive block technique and a fast sit-to-stand-to-sit task. IMU data were processed using an ad hoc adaptive Kaman filter, and pitch angular displacements were obtained and compared to stereophotogrammetric reference estimates. Tuning of the algorithm parameters was performed and relevant accuracy was tested in terms of root mean squared difference (RMSD) and correlation coefficient. Strong correlation (>0.978) were observed for both motor tasks, together with RMSD smaller than 4.4±1.7 deg. The tuned algorithm proved to be neither subject- nor task-specific (p>0.05).